2016
DOI: 10.1186/s13059-016-1062-5
|View full text |Cite
|
Sign up to set email alerts
|

CellMapper: rapid and accurate inference of gene expression in difficult-to-isolate cell types

Abstract: We present a sensitive approach to predict genes expressed selectively in specific cell types, by searching publicly available expression data for genes with a similar expression profile to known cell-specific markers. Our method, CellMapper, strongly outperforms previous computational algorithms to predict cell type-specific expression, especially for rare and difficult-to-isolate cell types. Furthermore, CellMapper makes accurate predictions for human brain cell types that have never been isolated, and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…We previously determined that INAVA is strongly enriched in simple epithelial cells ( Nelms et al, 2016 ) - the cell type that forms mucosal barriers. By domain analysis, the molecule has a single distinguishing feature, the Domain of Unknown Function DUF3338 (which we rename CUPID for Cytohesin Ubiquitin Protein Inducing Domain).…”
Section: Introductionmentioning
confidence: 99%
“…We previously determined that INAVA is strongly enriched in simple epithelial cells ( Nelms et al, 2016 ) - the cell type that forms mucosal barriers. By domain analysis, the molecule has a single distinguishing feature, the Domain of Unknown Function DUF3338 (which we rename CUPID for Cytohesin Ubiquitin Protein Inducing Domain).…”
Section: Introductionmentioning
confidence: 99%
“…As a second set of candidate genes, we identified genes implicated in epithelial trafficking by one of four indirect lines of evidence: (1) intracellular location, where the gene was localized to the endosomal system by proteomics ( Foster et al, 2006 ; Lapierre et al, 2007 ; Cao et al, 2008 ) or by GFP tagging ( Huh et al, 2003 ); (2) protein domain, where the gene contains at least one protein domain implicated in membrane trafficking or endosome dynamics (e.g., Rab GTPase, FYVE-finger, and BAR; Table S2); (3) expression in polarized epithelial cells, where the gene was found to be strongly expressed in simple columnar epithelial cells relative to other cell types ( Nelms et al, 2016 ); and (4) functional phenotype, where the gene was identified in either of two genome-wide RNAi screens for regulators of endocytic trafficking ( Balklava et al, 2007 ; Collinet et al, 2010 ). Each line of evidence highlighted several established epithelial trafficking genes, and we considered any gene identified in two or more searches to be a potential candidate for our screen ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, there are three isoforms of Par6 ( PARD6A , PARD6B , and PARD6G ), and it is unclear to what extent these operate differently in establishing cell polarity or regulating membrane trafficking. PARD6B was the only isoform included in our screen, and it was included because it was predicted to be strongly expressed in polarized epithelia ( Nelms et al, 2016 ). Indeed, antibody staining from the human protein atlas ( http://www.proteinatlas.org/ ; Uhlén et al, 2015 ) showed that PARD6B was strongly enriched in simple epithelia, whereas the other two Par6 isoforms were not.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, functional genomic networks have been built to study tissue- and cell type-specific genes’ interactions at the system-level [24]. In addition, tools for assessing cell type-specific changes in expression data are now also available [2528]. These tools pave the way for understanding the critical similarities and differences between affected tissues in SSc – and thus, clinical manifestations – and ultimately how cellular state and tissue microenvironment give rise to SSc manifestations (e.g., skin fibrosis).…”
Section: Systems Biology Of Ssc Data Integration and The Importancementioning
confidence: 99%